1998
DOI: 10.1111/j.1600-0749.1998.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultures of Skin Fragments of Salamandra salamandra salamandra (L.) Larvae

Abstract: As part of a study on the pigmentary system of Salamandra salamandra salamandra (L.), we cultured skin fragments of 7-10-day-old larvae in order to examine the expression of molecules implicated in cellular adhesion and migration and in regulating cell-cell relationships. Keratinocytes, fibroblasts, Leydig cells, xanthophores, and melanophores migrated from the fragments and were observed in the outgrowth. Keratinocytes and fibroblasts organized into an epidermal layer and an underlying "dermal portion." The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…This results in a higher pigmentation of the skin due to the dispersion of melanosomes into the melanophore's fingers, and the synthesis of pigments. In fire salamander larvae, all three types of chromatophores are scattered in the subepidermal collagen layer, and melanophores are regularly distributed in the epidermis (Pederzoli & Restani, ), which allows a uniform response to the background albedo. To understand how the background effect can be carried over, it is important to know that during metamorphosis the chromatophores are disposed of in a pattern resembling the adult coloration pattern (Pederzoli et al,).…”
Section: Discussionmentioning
confidence: 99%
“…This results in a higher pigmentation of the skin due to the dispersion of melanosomes into the melanophore's fingers, and the synthesis of pigments. In fire salamander larvae, all three types of chromatophores are scattered in the subepidermal collagen layer, and melanophores are regularly distributed in the epidermis (Pederzoli & Restani, ), which allows a uniform response to the background albedo. To understand how the background effect can be carried over, it is important to know that during metamorphosis the chromatophores are disposed of in a pattern resembling the adult coloration pattern (Pederzoli et al,).…”
Section: Discussionmentioning
confidence: 99%
“…Fukuzawa and Obika (20) report the expression of the cell adhesion molecules in cultures of xanthophores of Orizias latipes and X. laevis . More recently, Pederzoli and Restani (34) observed that some signal molecules such as CAMs, FN and β 1 ‐integrin are expressed in vitro by elements in the larval skin of S. s. salamandra (fibroblasts, keratinocytes and xanthophores). Fibronectin and VN are among the molecules permissive for movement and cell migration.…”
Section: Discussionmentioning
confidence: 99%